First repairing material, second repairing material and repairing method

By formulating repair materials with chemical components matching those of induction furnace components within a 10% mass difference, the repair materials address the issue of thermal expansion coefficient mismatch, reducing crack occurrence and enhancing repair durability.

JP2025062152AInactive Publication Date: 2025-04-14TYK CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023171030
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-02
Publication Date
2025-04-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional repair materials for induction furnace sleeves or crucibles do not consider the chemical component mismatch between the repair target and the repair material, leading to potential cracks and peeling under high temperature conditions.

Method used

The development of repair materials with specific chemical components, such as aluminum oxide, magnesium oxide, and silicon dioxide, that match the composition of the induction furnace components within a 10% mass difference, reducing the linear thermal expansion coefficient mismatch and enhancing repair durability.

Benefits of technology

The proposed repair materials effectively reduce crack occurrence and enhance repair effectiveness by minimizing thermal expansion coefficient differences, ensuring the induction furnace maintains functionality even under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062152000001_ABST
    Figure 2025062152000001_ABST
Patent Text Reader

Abstract

To provide a repairing material highly effective in repairing by including a component and a ratio adaptable to a chemical component possessed by a repaired object, and a repairing method using the repairing material.SOLUTION: A first repairing material 1 is a repairing material usable for a sleeve or a crucible that includes a specified chemical component among materials formed in an induction furnace that melts metal. The first repairing material 1 includes powders 2. A range of difference between mass% of the specified chemical component included in the powders 2 and mass% of the specified chemical component included in the sleeve or the crucible of the repaired object is within 10%. The powders 2 can produce a mix material 3.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a repair material for use with sleeves or crucibles for induction furnaces for melting metals, and to a method for repairing damaged sleeves or crucibles. [Background technology]

[0002] Conventionally, when the sleeve or crucible wall formed in an induction furnace for melting metal is damaged, a repair material and a repair method using the repair material have been proposed. For example, Patent Document 1 proposes a hot repair method for industrial furnaces, characterized in that a powdered repair material mainly composed of 5 to 30 mass% metal powder, 10 to 40 mass% of one or more selected from copper oxide, iron oxide, and oxidizer, and the remainder refractory powder, is sprayed onto the surface to be repaired at high temperature using a non-oxygen gas such as nitrogen gas, carbon dioxide gas, or inert gas as a carrier gas.

[0003] The repair material contains a specific amount of copper oxide, iron oxide or oxide, which acts as a combustion-supporting substance. After being sprayed onto the surface, the metal powder oxidizes in a high-temperature atmosphere and melts and adheres due to the reaction heat. As a result, a dense repair body can be formed, similar to the conventional method using oxygen gas as a carrier gas.

[0004] Copper oxide or iron oxide releases oxygen more easily than normal oxides, and this is thought to be why it functions sufficiently as a combustion-supporting substance in the proposal of Patent Document 1. On the other hand, oxidizing agents act as a combustion-supporting substance due to their inherent properties.

[0005] A non-oxygen gas is used as the carrier gas for transporting the repair material. Although the generation of static electricity, which can become a source of fire, is unavoidable within the transport pipe, the use of a non-oxygen gas completely eliminates the possibility of the repair material catching fire within the transport pipe.

[0006] The method described in Patent Document 1 is intended for hot repair, where the surface to be repaired is in a high temperature state due to residual heat from a furnace. In cold repair, the oxidation reaction of the metal powder is insufficient, and the effect of the present invention cannot be obtained. It is described that in order to obtain a sufficient repair effect, it is preferable that the temperature of the surface to be repaired is, for example, 700°C or higher.

[0007] This configuration completely eliminates the risk of the repair material catching fire inside the transfer pipe, which was seen in the conventional method that used oxygen gas as the carrier gas, and the adhesion and density of the applied body are comparable. In addition, it is said that the application equipment can be made smaller and simpler, which not only reduces equipment costs but also enables quick application due to its easy handling. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent Publication No. 2004-28504 Summary of the Invention [Problem to be solved by the invention]

[0009] However, in the conventional example described in Patent Document 1, the relationship between the chemical components contained in the repair object including the repaired surface and the chemical components of the repair material is not taken into consideration. Therefore, the expansion coefficient may differ between the repaired surface and the repair material used for repairing the surrounding area, and cracks may occur due to temperature changes. Induction furnaces that melt metals reach high temperatures of 700°C or more during use. Therefore, if cracks or peeling occur in the repaired area in a high-temperature environment, the induction furnace will no longer function.

[0010] An object of the present invention is to provide a repair material that has a high repair effect by having ingredients and ratios suitable for the chemical components of the object to be repaired, and a repair method using said repair material. [Means for solving the problem]

[0011] A first repair material according to a first aspect of the present invention is a repair material capable of repairing a sleeve or crucible containing a specific chemical component, which is one of the components formed in an induction furnace for melting metal, and comprises a powder, the difference between the mass percentage of the specific chemical component contained in the powder and the mass percentage of the specific chemical component contained in the sleeve or crucible to be repaired being within a range of 10%, and the powder is capable of producing a kneading material.

[0012] According to this, the first repair material according to the first aspect of the present invention has a difference of 10% or less between the mass % of the specific chemical component contained in the powder and the mass % of the specific chemical component contained in the sleeve or crucible to be repaired. Then, when the first repair material is mixed, the difference in linear thermal expansion coefficient between the mixed material and the repair object becomes small. Therefore, when the mixed material that can be generated by the first repair material is applied and / or filled to the repair area, the occurrence of cracks can be reduced even if the repair area is exposed to a temperature change after repair, and the repair effect can be improved.

[0013] The specific chemical component of the first repair material may be aluminum oxide. In this case, the powder contains aluminum oxide, and the difference between the mass % of aluminum oxide contained in the powder and the mass % of aluminum oxide contained in the sleeve or crucible to be repaired is within 10%. Then, the difference in linear thermal expansion coefficient between the kneaded material and the repair object when the first repair material is kneaded is small. Therefore, the kneaded material that can be generated by the first repair material can reduce the occurrence of cracks even if the repaired area is exposed to temperature changes after repair, and can enhance the repair effect.

[0014] The specific chemical component of the first repair material may be magnesium oxide. In this case, the powder contains magnesium oxide, and the difference between the mass % of magnesium oxide contained in the powder and the mass % of magnesium oxide contained in the sleeve or crucible to be repaired is within 10%. Then, the difference in linear thermal expansion coefficient between the kneaded material and the repair object when the first repair material is kneaded is small. Therefore, the kneaded material that can be generated by the first repair material can reduce the occurrence of cracks even if the repaired area is exposed to temperature changes after repair, and can enhance the repair effect.

[0015] The specific chemical component of the first repair material may be silicon dioxide. In this case, the powder contains silicon dioxide, and the difference between the mass % of silicon dioxide contained in the powder and the mass % of silicon dioxide contained in the sleeve or crucible to be repaired is within 10%. Then, the difference in linear thermal expansion coefficient between the kneaded material and the repair object when the first repair material is kneaded is small. Therefore, the kneaded material that can be generated by the first repair material can reduce the occurrence of cracks even if the repaired area is exposed to temperature changes after repair, and can enhance the repair effect.

[0016] The powder of the first repair material may have a maximum particle size of 1 mm or less, and may contain 30% or more particles with a particle size of less than 0.1 mm. In this case, the powder is easy to handle. Also, the powder can be used to easily generate a kneading material at the construction site. Also, since the particles are fine, the generated kneading material can be filled into the fine details of the damaged area. This can improve the repair effect.

[0017] The powder of the first repair material may have a maximum particle size of 1 mm or less, and may contain particles with a particle size of less than 0.1 mm in a range of 40% to 60%. In this case, the first repair material is easier to handle, and it is easy to produce a kneaded material with excellent workability. In addition, since the particles are fine, the kneaded material produced can be filled into the fine details of the damaged area. This improves the repair effect.

[0018] A second repair material according to a second aspect of the present invention is a repair material capable of repairing a sleeve or crucible containing a specific chemical component, which is one of the components formed in an induction furnace for melting metal, and comprises a kneading material, and the difference between the mass percentage of the specific chemical component contained in the kneading material and the mass percentage of the specific chemical component contained in the sleeve or crucible to be repaired is within 10%, relative to the specific chemical component contained in the sleeve or crucible.

[0019] According to this, the difference between the mass% of the specific chemical components contained in the second repair material according to the second aspect of the present invention and the mass% of the specific chemical components contained in the repair object is within 10%. Therefore, the difference in the linear thermal expansion coefficient between the repair object and the second repair material is small, so that even if the kneaded material at the repaired portion is exposed to a temperature change after repair with the second repair material, the occurrence of cracks can be reduced and the repair effect can be improved.

[0020] The second repair material may have aluminum oxide as the specific chemical component. In this case, the difference between the mass% of aluminum oxide contained in the kneading material and the mass% of aluminum oxide contained in the sleeve or crucible to be repaired is within 10%. Therefore, the difference in linear thermal expansion coefficient between the repair object and the second repair material is small, so that even if the kneading material at the repaired portion is exposed to a temperature change after repair with the second repair material, the occurrence of cracks can be reduced and the repair effect can be improved.

[0021] The second repair material may have magnesium oxide as the specific chemical component. In this case, the difference between the mass% of magnesium oxide contained in the kneading material and the mass% of magnesium oxide contained in the sleeve or crucible to be repaired is within 10%. Therefore, the difference in the linear thermal expansion coefficient between the repair object and the second repair material is small, so that even if the kneading material at the repaired portion is exposed to a temperature change after repair with the second repair material, the occurrence of cracks can be reduced and the repair effect can be improved.

[0022] The second repair material may have the specific chemical component be silicon dioxide. In this case, the difference between the mass% of silicon dioxide contained in the kneading material and the mass% of silicon dioxide contained in the sleeve or crucible to be repaired is within 10%. Therefore, the difference in the linear thermal expansion coefficient between the repair object and the second repair material is small, so that even if the kneading material at the repaired portion is exposed to a temperature change after repair with the second repair material, the occurrence of cracks can be reduced and the repair effect can be improved.

[0023] The difference between the linear thermal expansion coefficient of the kneaded material at 1500° C. and the linear thermal expansion coefficient of the sleeve or the crucible to be repaired at 1500° C. may be within a range of 0.5%. In this case, even if the kneaded material at the repaired portion is exposed to a temperature change after repair, cracks caused by the difference in linear thermal expansion coefficient can be further reduced, and the repair effect can be improved.

[0024] A repair method according to a third aspect of the present invention is a method for repairing a sleeve or crucible containing a specific chemical component among components formed in an induction furnace for melting metal, and includes a first step of selecting a first repair material having a powder, a second step of kneading the first repair material with a sodium silicate aqueous solution to produce a second repair material, and a third step of applying and / or filling the second repair material to the repair target of the sleeve or the crucible, wherein the first repair material selected in the first step has a difference between the mass % of the specific chemical component contained in the powder and the mass % of the specific chemical component contained in the sleeve or the crucible that is the repair target within a range of 10%.

[0025] According to this, in the repair method according to the third aspect of the present invention, the first repair material selected in the first step has a difference in mass% of the specific chemical component contained in the powder and the mass% of the specific chemical component contained in the sleeve or crucible to be repaired within a range of 10%. The second repair material is produced by kneading the first repair material with a sodium silicate aqueous solution, so the difference in mass% of the specific chemical component contained in the repair object is small. Therefore, the repair method can reduce cracks even if the second repair material is exposed to temperature changes after repair.

[0026] The specific chemical component may be aluminum oxide. In this case, the difference between the mass % of aluminum oxide contained in the first repair material and the mass % of aluminum oxide contained in the sleeve or crucible to be repaired is within 10%. The second repair material is produced by kneading the first repair material with a sodium silicate aqueous solution, so the difference between the mass % of aluminum oxide contained in the repair object is small. Therefore, the repair method can reduce cracks even if the second repair material is exposed to temperature changes after repair.

[0027] The specific chemical component may be magnesium oxide. In this case, the difference between the mass % of magnesium oxide contained in the first repair material and the mass % of magnesium oxide contained in the sleeve or crucible to be repaired is within 10%. The second repair material is produced by kneading the first repair material with a sodium silicate aqueous solution, so the difference between the mass % of magnesium oxide contained in the repair object is small. Therefore, the repair method can reduce cracks even if the second repair material is exposed to temperature changes after repair.

[0028] The specific chemical component may be silicon dioxide. In this case, the difference between the mass% of silicon dioxide contained in the first repair material and the mass% of silicon dioxide contained in the sleeve or crucible to be repaired is within 10%. The second repair material is produced by kneading the first repair material with a sodium silicate aqueous solution, so the difference between the mass% of silicon dioxide contained in the repair object is small. Therefore, the repair method can reduce cracks even if the second repair material is exposed to temperature changes after repair.

[0029] In addition, the repair method may be such that the difference between the linear thermal expansion coefficient at 1500°C of the second repair material applied and / or filled to the sleeve or crucible to be repaired and the linear thermal expansion coefficient at 1500°C of the sleeve or crucible to be repaired is 0.5% or less.

[0030] In this case, since the difference in linear thermal expansion coefficient between the repair object and the kneaded material is small, even if the kneaded material at the repaired area is exposed to temperature changes after repair, cracks caused by the difference in linear thermal expansion coefficient can be reduced, and the repair effect can be improved. [Brief description of the drawings]

[0031] [Figure 1] FIG. 1 is a cross-sectional view of a state in which a kneading material 3 is applied and / or filled onto a sleeve 16 of an induction furnace 15, which is an object to be repaired by a first repair material 1 and a second repair material 11 of the present invention. [Diagram 2] FIG. 2 is a diagram for explaining a method of kneading the powders 2, 22 of the first repair material 1 of the present invention with a sodium silicate aqueous solution 4 to produce a kneaded material 3, which is then used as a second repair material 11. [Diagram 3] 1 is a diagram comparing the mass % of the chemical components of the sleeve 16, etc., which is the repair target, with the mass % of the main chemical components of the powders 2, 22 in the first repair material 1, and others. [Figure 4] 1 is a diagram comparing the mass % of main chemical components and the linear thermal expansion coefficient at 1500° C. between a sleeve 16 etc. that is the repair target and the kneaded material 3 in the second repair material 11. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] Hereinafter, the first repair material 1, the second repair material 11, and the repair method embodying the present invention will be described with reference to the drawings. Note that the description of the embodiment of the invention and the drawings referred to are used to explain the technical features that the present invention can adopt. The present invention is not limited to these. The configurations shown in the drawings are merely illustrative examples and are not intended to limit the present invention.

[0033] <Description of the first repair material 1 according to the first aspect of the present invention> A first repair material 1 according to a first embodiment of the present invention will be described with reference to the drawings. The first repair material 1 is a repair material that can be used for a sleeve 16 or a crucible containing a specific chemical component among the members formed in an induction furnace 15 for melting metal. The first repair material 1 includes a powder 2. As shown in FIG. 3, the specific chemical component is, for example, aluminum oxide, magnesium oxide, and silicon dioxide, but may be another chemical component. The difference between the mass % of the specific chemical component contained in the powder 2 and the mass % of the specific chemical component contained in the sleeve 16 or the crucible to be repaired is within 10%.

[0034] As shown in Fig. 2, the powder 2 can generate the kneading material 3. The kneading material 3 is preferably generated by kneading the powder 2 of the first repair material 1 with a sodium silicate aqueous solution 4. Note that the material to be kneaded with the powder 2 may be other than the sodium silicate aqueous solution 4 as long as it can be kneaded.

[0035] A case where the specific chemical component contained in the sleeve 16 or the crucible is aluminum oxide will be described. In this case, the first repair material 1 can be used for the sleeve 16 containing aluminum oxide or the crucible containing aluminum oxide. As shown in FIG. 3, the first repair material 1 includes a powder 2 containing aluminum oxide, and the difference between the mass % of aluminum oxide contained in the powder 2 and the mass % of aluminum oxide contained in the sleeve 16 or the crucible to be repaired is within 10%. As an example, the aluminum oxide contained in the sleeve A1 is 70 mass %, and the aluminum oxide contained in the repair material A2 of the first repair material 1 is 75.7%. As shown in FIG. 2, the powder 2 can generate a kneading material 3 with the sodium silicate aqueous solution 4. Note that the repair materials A2, B2, C2, D2, E2, and F2 shown in FIG. 3 are examples of the first repair material 1. Also, the sleeves A1, B1, C1, D1, E1, and F1 are examples of the sleeve 16.

[0036] Next, a case where the specific chemical component contained in the sleeve 16 or the crucible is magnesium oxide will be described. In this case, the first repair material 1 can be used for the sleeve 16 containing magnesium oxide or the crucible containing magnesium oxide. As shown in FIG. 3, the first repair material 1 includes a powder 2 containing magnesium oxide, and the difference between the mass % of magnesium oxide contained in the powder 2 and the mass % of magnesium oxide contained in the sleeve 16 or the crucible to be repaired is within 10%. As an example, the magnesium oxide contained in the sleeve A1 is 26.2 mass %, and the magnesium oxide contained in the repair material A2 of the first repair material 1 is 23.6 mass %.

[0037] Next, a case where the specific chemical component contained in the sleeve 16 or the crucible is silicon dioxide will be described. In this case, the first repair material 1 can be used for the sleeve 16 containing silicon dioxide or the crucible containing silicon dioxide. As shown in FIG. 3, the first repair material 1 includes a powder 2 containing silicon dioxide, and the difference between the mass % of silicon dioxide contained in the powder 2 and the mass % of silicon dioxide contained in the sleeve 16 or the crucible to be repaired is within 10%. As an example, the silicon dioxide contained in the sleeve A1 is 1.7 mass %, and the magnesium oxide contained in the repair material A2 of the first repair material 1 is 0.2%.

[0038] In addition to the above, as shown in FIG. 3, the powder 2 may have a maximum particle size of 1 mm or less and contain 30% or more particles with a particle size of less than 0.1 mm. More preferably, the powder 2 may have a maximum particle size of 1 mm or less and contain particles with a particle size of less than 0.1 mm in a range of 40% to 60%. Here, 0.1 mmF (%) in FIG. 3 is a numerical value indicating the proportion of particles with a particle size of less than 0.1 mm in the powder 2. In the example shown in FIG. 3, the proportion of particles with a particle size of less than 0.1 mm is 53.4% ​​for repair material A2, 52.4% for repair material B2, 51.1% for repair material C2, 40.6% for repair material D2, 43.1% for repair material E2, and 33.8% for repair material F2.

[0039] <Effects of the first repair material 1 according to the first aspect of the present invention> The first repair material 1 according to the first aspect of the present invention described above has the following effects. In the first repair material 1, the difference between the mass % of the specific chemical component contained in the powder 2 and the mass % of the specific chemical component contained in the sleeve 16 or crucible to be repaired is within 10%. Then, the difference in linear thermal expansion coefficient between the kneaded material 3 produced when the first repair material 1 is kneaded and the repair object becomes small. Therefore, when the kneaded material 3 that can be generated by the first repair material 1 is applied and / or filled to the repair area, the occurrence of cracks can be reduced even if the repair area is exposed to a temperature change after repair, and the repair effect can be improved.

[0040] Also, when the specific chemical component is aluminum oxide, as shown in FIG. 3, the difference between the mass % of aluminum oxide contained in the powder 2 and the mass % of aluminum oxide contained in the sleeve 16 or crucible to be repaired is within 10% in the first repair material 1. Then, the kneaded material 3 produced when the first repair material 1 is kneaded has a small difference in linear thermal expansion coefficient between the repair object and the kneaded material 3. Therefore, the kneaded material 3 that can be generated by the first repair material 1 can reduce the occurrence of cracks even if the repaired part is exposed to a temperature change after repair, and can improve the repair effect. In the example shown in FIG. 3 and FIG. 4, the mass % of aluminum oxide in the sleeves A1, B1, D1, and E1 is the highest, so the repair effect is particularly high. This is because the smaller the difference in mass % between the chemical components mainly contained in the sleeve 16 or crucible to be repaired and the main chemical components of the kneaded material 3 used for repair, the smaller the difference in linear thermal expansion coefficient.

[0041] As will be described later with reference to FIG. 3 and FIG. 4, the difference in mass% of the main chemical components contained in the powder 2 and the kneaded material 3 obtained by kneading the powder 2 and the sodium silicate aqueous solution 4 is small. For example, as shown in FIG. 3, the mass% of aluminum oxide in the repair material A2 of the first repair material 1 is 75.7%, and as shown in FIG. 4, the mass% of aluminum oxide in the repair material A3 of the second repair material 11 is 68.5%. The difference in mass% between the two is 7.2%. The difference in mass% between the repair material A2 and the repair material A3 is 5.7% and 1.5%. That is, when the first repair material 1 is kneaded with the sodium silicate aqueous solution 4 to produce the second repair material 11, the change in mass% of aluminum oxide between the two is small. This is not limited to aluminum oxide, but also applies to magnesium oxide and silicon dioxide.

[0042] That is, the first repair material 1 including the powder 2 has a mass percentage of the specific chemical component that is within a 10% difference from the mass percentage of the specific chemical component contained in the sleeve 16 or crucible to be repaired. Then, the second repair material 11 kneaded with the first repair material 1 has a mass percentage of the specific chemical component that is within a 10% difference from the mass percentage of the specific chemical component contained in the sleeve 16 or crucible to be repaired. Therefore, the difference in the linear thermal expansion coefficient is small.

[0043] Also, when the specific chemical component is magnesium oxide, as shown in FIG. 3, the difference between the mass % of magnesium oxide contained in the powder 2 of the first repair material 1 and the mass % of magnesium oxide contained in the sleeve 16 or crucible to be repaired is within 10%. Then, the kneaded material 3 obtained when the first repair material 1 is kneaded with the sodium silicate aqueous solution 4 has a small difference in linear thermal expansion coefficient between the first repair material 1 and the repair object. Therefore, the kneaded material 3 that can be generated by the first repair material 1 can reduce the occurrence of cracks even if the repaired part is exposed to a temperature change after repair, and can improve the repair effect. In the example shown in FIG. 3 and FIG. 4, the sleeve C1 has the highest mass % of magnesium oxide, and the sleeves A1, B1, and E1 have the second highest mass % of magnesium oxide, so the repair effect is particularly high.

[0044] Also, when the specific chemical component is silicon dioxide, as shown in FIG. 3, the difference between the mass % of silicon dioxide contained in the powder 2 of the first repair material 1 and the mass % of silicon dioxide contained in the sleeve 16 or crucible to be repaired is within 10%. Then, the difference in linear thermal expansion coefficient between the kneading material 3 when the first repair material 1 is kneaded with the sodium silicate aqueous solution 4 and the repair object becomes small. Therefore, the repaired part repaired with the kneading material 3 can reduce the occurrence of cracks even if it is exposed to a temperature change after repair, and the repair effect can be improved. In the example shown in FIG. 3 and FIG. 4, the sleeve F1 has the highest mass % of silicon dioxide, so the repair effect is particularly high.

[0045] The effects described above have been described individually for the specific chemical components contained in the sleeve 16 or the crucible to be repaired. Even if the sleeve 16 or the crucible to be repaired contains a plurality of specific chemical components, the first repair material 1 will have a repair effect if it satisfies the requirements described above for one specific chemical component.

[0046] On the other hand, when the sleeve 16 or the crucible contains multiple chemical components, it is more effective if the difference between the mass% of all the main chemical components and the mass% of all the main chemical components contained in the powder 2 of the first repair material 1 is within 10%. In the example shown in FIG. 3, the sleeves A1 to F1 and the repair materials A2 to F2 of the first repair material 1 have three main chemical components: aluminum oxide, magnesium oxide, and silicon dioxide. The difference in mass% for all three types of chemical components is within 10%. Therefore, even if the repaired area is exposed to temperature changes after repair, cracks caused by the difference in linear thermal expansion coefficient can be reduced, and the repair effect can be improved.

[0047] 3, the sleeve 16 or crucible to be repaired often contains aluminum oxide. The first repair material 1 corresponds to the repair object and may contain magnesium oxide and / or silicon dioxide in addition to aluminum oxide. If the difference in mass percentage between the first repair material 1 and the aluminum oxide and / or magnesium oxide and / or silicon dioxide contained in the repair object is within 10%, the first repair material 1 has a greater repair effect than when only aluminum oxide is contained.

[0048] In addition, even if the sleeve 16 or the crucible contains multiple chemical components, the difference in mass% between all the chemical components contained in the powder 2 of the first repair material 1 does not necessarily need to be within 10%. For example, when the sleeve 16 or the crucible contains three main chemical components, among which aluminum oxide accounts for a large proportion, the repair effect is high if the difference in mass% between the aluminum oxide contained in the powder 2 of the first repair material 1 is within 10%. When the sleeve 16 or the crucible contains other chemical components for a large proportion, the repair effect is achieved if the difference in mass% between the other chemical components contained in the powder 2 of the first repair material 1 is within 10%. In other words, the first repair material 1 has a repair effect if the difference in mass% between the chemical components contained in the repair target and the components with the larger mass% is within 10%.

[0049] As shown in Fig. 3, the powder 2 of the first repair material 1 is easy to handle if it has a maximum particle size of 1 mm or less and contains 30 mass % or more of particles with a particle size of less than 0.1 mm. The powder 2 can be easily mixed with a sodium silicate aqueous solution 4 at the construction site to produce the admixture 3. If the particles are fine, the admixture 3 can be filled into the fine details of the damaged area, as shown in Fig. 1. This can improve the repair effect.

[0050] As shown in FIG. 3, the powder 2 of the first repair material 1 preferably has a maximum particle size of 1 mm or less, and particles with a particle size of less than 0.1 mm are between 40% and 60% by mass, making it easier to handle and easier to produce a kneaded material 3 with a sodium silicate aqueous solution 4 that has excellent workability. The first repair material 1 contains a certain percentage of particles with a particle size of 0.1 mm or more and 1 mm or less, making it easier to knead than when all particles are less than 0.1 mm. In addition, since the particles are fine, the kneaded material 3 produced can be filled into the fine details of the damaged area, as shown in FIG. 1. Therefore, in addition to the effects already described, the repair effect can be further improved.

[0051] <Description of the second repair material 11 according to the second embodiment of the present invention> Next, a second repair material 11 according to a second embodiment of the present invention will be described. The second repair material 11 is a repair material capable of repairing a sleeve 16 or a crucible containing a specific chemical component among the members formed in an induction furnace 15 for melting metal. The second repair material 11 includes a kneading material 3. With respect to the specific chemical component contained in the sleeve 16 or the crucible, the difference range between the mass% of the specific chemical component contained in the kneading material 3 and the mass% of the specific chemical component contained in the sleeve 16 or the crucible to be repaired is within 10%.

[0052] The repair materials A3, B3, C3, D3, E3, and F3 shown in FIG. 4 are examples of the second repair material 11. The specific chemical components are, for example, aluminum oxide, magnesium oxide, and silicon dioxide, but may be other chemical components. As already described, the kneading material 3 is, for example, produced by kneading the powder 2 of the first repair material 1 and the sodium silicate aqueous solution 4. However, the production process of the kneading material 3 is not limited to this, and the kneading material 3 may be produced by other methods. As shown in the example of FIG. 4, the kneading material 3 may have a mass % difference of 10% or less with respect to the specific chemical components contained in the sleeve 16, etc., which is the repair target.

[0053] The second repair material 11 includes both a state before repair in which it can be applied or / and filled to the repair target, and a state after repair in which the repair target has been repaired. That is, the difference in mass % between the specific chemical components contained in the second repair material 11 and the specific chemical components contained in the sleeve 16 or the like that is the repair target is within 10% in both the state before repair and the state after repair.

[0054] Furthermore, when the specific chemical component is aluminum oxide, the second repair material 11 can repair a sleeve 16 or a crucible containing aluminum oxide. As shown in FIG. 4, the second repair material 11 includes a kneading material 3 containing aluminum oxide. The difference between the mass % of aluminum oxide contained in the kneading material 3 and the mass % of aluminum oxide contained in the sleeve 16 or the crucible to be repaired is within 10%. The second repair material 11 can be applied and / or filled to the sleeve 16 or the crucible to be repaired.

[0055] Furthermore, when the specific chemical component is magnesium oxide, the second repair material 11 can repair a sleeve 16 or a crucible containing magnesium oxide. As shown in Fig. 4, the second repair material 11 includes a kneading material 3 containing magnesium oxide. The difference between the mass % of magnesium oxide contained in the kneading material 3 and the mass % of magnesium oxide contained in the sleeve 16 or the crucible to be repaired is within a range of 10%. The second repair material 11 can be applied and / or filled to the sleeve 16 or the crucible to be repaired.

[0056] Furthermore, when the specific chemical component is silicon dioxide, the second repair material 11 can repair the sleeve 16 or crucible containing silicon dioxide. As shown in FIG. 4, the second repair material 11 includes a kneading material 3 containing silicon dioxide. The difference between the mass % of silicon dioxide contained in the kneading material 3 and the mass % of silicon dioxide contained in the sleeve 16 or crucible is within 10%. The second repair material 11 can be applied and / or filled to the sleeve 16 or crucible to be repaired.

[0057] The difference between the linear thermal expansion coefficient of the kneading material 3 at 1500°C and the linear thermal expansion coefficient of the sleeve 16 or crucible to be repaired at 1500°C is within 0.5%. This applies to all of the repair materials A3 to F3, which are the second repair material 11 described as the second embodiment. Here, the linear thermal expansion coefficient is measured at 1500°C using a measuring device and a measuring method conforming to JIS R2207-3.

[0058] <Effects of the second repair material 11 according to the second aspect of the present invention> The second repair material 11 according to the second aspect of the present invention described above has the following effects. The second repair material 11 can be applied and / or filled to the sleeve 16 or crucible that is the repair target. The difference between the mass % of the specific chemical component contained in the second repair material 11 and the mass % of the specific chemical component contained in the repair target is within 10%. Therefore, since the difference in the linear thermal expansion coefficient between the repair target and the second repair material 11 is small, even if the kneaded material 3 at the repaired portion is exposed to a temperature change after repair with the second repair material 11, the occurrence of cracks can be reduced and the repair effect can be improved.

[0059] Furthermore, when the specific chemical component is aluminum oxide, as shown in Fig. 4, the difference between the mass % of aluminum oxide in the kneading material 3 and the mass % of aluminum oxide contained in the repair target is within 10% in the second repair material 11. Therefore, the difference in the linear thermal expansion coefficient between the repair target and the kneading material 3 is small, so that even if the kneading material 3 at the repaired portion is exposed to a temperature change after repair, the occurrence of cracks can be reduced and the repair effect can be improved. Furthermore, the second repair material 11 can be used directly for repair as long as it is in a state where it can be applied and / or filled to the repair target of the sleeve 16 or the crucible.

[0060] Furthermore, when the specific chemical component is magnesium oxide, the difference between the mass % of magnesium oxide contained in the kneaded material 3 and the mass % of magnesium oxide contained in the repair target is within 10%, as shown in Fig. 4. Therefore, the difference in the linear thermal expansion coefficient between the repair target and the kneaded material 3 is small, so that even if the kneaded material 3 at the repaired portion is exposed to a temperature change after repair, the occurrence of cracks can be reduced and the repair effect can be improved. Furthermore, the second repair material 11 can be used directly for repair as long as it is in a state where it can be applied and / or filled to the repair target of the sleeve 16 or the crucible.

[0061] Furthermore, when the specific chemical component is silicon dioxide, as shown in Fig. 4, the difference between the mass % of silicon dioxide contained in the kneading material 3 and the mass % of silicon dioxide contained in the repair object is within 10%. Therefore, the difference in the linear thermal expansion coefficient between the repair object and the kneading material 3 is small, so that even if the kneading material 3 at the repaired portion is exposed to a temperature change after repair, the occurrence of cracks can be reduced and the repair effect can be improved. Furthermore, the second repair material 11 can be used directly for repair as long as it is in a state where it can be applied and / or filled to the repair object of the sleeve 16 or the crucible.

[0062] The effects described above have been described individually for the specific chemical components contained in the sleeve 16 or the crucible to be repaired. Even if the sleeve 16 or the crucible to be repaired contains a plurality of specific chemical components, the second repair material 11 will have a repair effect if it satisfies the requirements described above for one specific chemical component.

[0063] On the other hand, when the sleeve 16 or the crucible contains multiple chemical components, it is more effective if the difference in mass% between all the main chemical components contained in the sleeve 16 or the crucible and the mass% between all the main chemical components contained in the kneading material 3 of the second repair material 11 is within 10%. In the example shown in Fig. 4, the sleeve 16 or the crucible and the kneading material 3 of the second repair material 11 mainly contain three types of chemical components, aluminum oxide, magnesium oxide, and silicon dioxide, and the difference in mass% for all three types of chemical components is within 10%. Therefore, even if the repaired area is exposed to a temperature change after repair, cracks caused by the difference in linear thermal expansion coefficient can be reduced, and the repair effect can be improved.

[0064] 4, the sleeve 16 or crucible to be repaired often contains aluminum oxide. The second repair material 11 corresponds to the repair object, and in addition to containing aluminum oxide, may contain magnesium oxide and / or silicon dioxide. If the difference in mass percentage between the aluminum oxide and the magnesium oxide and / or silicon dioxide contained in the repair object is within 10%, a greater repair effect is achieved compared to the case where only aluminum oxide is contained.

[0065] In addition, even if the sleeve 16 or the crucible contains a plurality of chemical components, the difference in mass% between the second repair material 11 and all the chemical components contained in the kneading material 3 does not necessarily have to be within 10%. For example, when the sleeve 16 or the crucible contains three main chemical components, among which aluminum oxide accounts for a large proportion, the repair effect is high if the difference in mass% between the second repair material 11 and the aluminum oxide contained in the kneading material 3 is within 10%. When the sleeve 16 or the crucible contains other chemical components for a large proportion, the repair effect is achieved if the difference in mass% between the second repair material 11 and the other chemical components contained in the kneading material 3 is within 10%. In other words, the second repair material 11 has a repair effect if the difference in mass% between the second repair material 11 and the component with the larger mass% among the chemical components contained in the repair target is within 10%.

[0066] In addition, as described above, by making the mass % difference between the chemical components mainly contained in the sleeve 16 or crucible to be repaired and the chemical components mainly contained in the kneading material 3 of the second repair material 11 within 10%, the following effect is achieved. That is, as shown in FIG. 4, the difference in linear thermal expansion coefficient at 1500°C between the sleeve 16 or crucible to be repaired and the kneading material 3 is 0.5% or less. For example, the linear thermal expansion coefficient at 1500°C of the sleeve A1 is 1.09%, and the linear thermal expansion coefficient at 1500°C of the repairing material A3 is 0.98%, so the difference is 0.11%. Therefore, even if the kneading material 3 at the repaired portion is exposed to a temperature change after repair, the second repairing material 11 can further reduce cracks caused by the difference in linear thermal expansion coefficient, and can enhance the repair effect. All of the repairing materials A3 to F3, which are the second repairing materials 11 described in the second embodiment, achieve this effect.

[0067] <Description of the repair method according to the third aspect of the present invention> Next, a repair method according to a third embodiment of the present invention will be described. The repair method is a method for repairing a sleeve 16 or a crucible formed in an induction furnace 15 for melting metal. The repair method includes a first step of selecting a first repair material 1 including a powder 2, a second step of kneading the first repair material 1 with a sodium silicate aqueous solution 4 to generate a second repair material 11, and a third step of applying and / or filling the second repair material 11 to the sleeve 16 or the crucible to be repaired. The first repair material 1 selected in the first step has a difference range of 10% between the mass % of a specific chemical component contained in the powder 2 and the mass % of a specific chemical component contained in the sleeve 16 or the crucible to be repaired.

[0068] The first repair material 1 is shipped from the factory in the form of powder 2. First, the first repair material 1 as the powder 2 to be selected for the repair object will be described. When repairing the repair object, the repairer selects the first repair material 1 corresponding to the chemical components of the target sleeve 16, etc. FIG. 3 shows a comparison between the mass % of the chemical components of the sleeve 16, etc. to be repaired and the mass % of the chemical components of the first repair material 1 in the form of powder 2 suitable for use.

[0069] Furthermore, the steps of the repair method will be described in detail. Before or at the same time as the first and second steps, anything adhering to the portion of the sleeve 16 or crucible to be repaired is removed. At that time, the surface becomes rough. Next, a sodium silicate aqueous solution 4 is applied to the portion to be repaired to improve adhesion. Next, in the third step, the second repair material 11 is applied on top of the sodium silicate aqueous solution 4. After that, it is left for about half a day to harden. Alternatively, it may be hardened by applying heat with a gas burner or the like. Finally, molten metal is poured into the sleeve 16 or crucible that has been repaired, and the repaired portion is hardened by heat.

[0070] Also, as shown in Fig. 3, when the specific chemical component is aluminum oxide, the first repair material 1 selected in the first step contains aluminum oxide. The difference between the mass % of aluminum oxide contained in the first repair material 1 and the mass % of aluminum oxide contained in the sleeve 16 or crucible to be repaired is within 10%. As shown in Fig. 4, the difference between the mass % of aluminum oxide contained in the second repair material 11 generated in the second step and the mass % of aluminum oxide contained in the sleeve 16 or crucible to be repaired is within 10%. That is, when the selected first repair material 1 and the sodium silicate aqueous solution 4 are kneaded, the second repair material 11 is generated as the kneading material 3.

[0071] Furthermore, as shown in Fig. 3, when the specific chemical component is magnesium oxide, the first repair material 1 selected in the first step contains magnesium oxide. The difference between the mass % of magnesium oxide contained in the first repair material 1 and the mass % of magnesium oxide contained in the sleeve 16 or crucible to be repaired is within 10%. As shown in Fig. 4, the difference between the mass % of magnesium oxide contained in the second repair material 11 generated in the second step and the mass % of magnesium oxide contained in the sleeve 16 or crucible to be repaired is within 10%.

[0072] Furthermore, as shown in Fig. 3, when the specific chemical component is silicon dioxide, the first repair material 1 selected in the first step contains silicon dioxide. The difference between the mass % of silicon dioxide contained in the first repair material 1 and the mass % of silicon dioxide contained in the sleeve 16 or crucible to be repaired is within 10%. As shown in Fig. 4, the difference between the mass % of silicon dioxide contained in the second repair material 11 generated in the second step and the mass % of silicon dioxide contained in the sleeve 16 or crucible to be repaired is within 10%.

[0073] Specifically, as shown in FIG. 3 already described, in the first step, repair materials A2 to F2 are selected for sleeves A1 to F1, respectively, such as repair material A2 for sleeve A1 and repair material B2 for sleeve B1. In the example shown in FIG. 3, the mass% difference between the repair materials A2 to F2 used is 10% or less for all of the chemical components, aluminum oxide, magnesium oxide, and silicon dioxide, which are mainly contained in sleeves A1 to F1. However, as explained in the selection of the first repair material 1 according to the first embodiment, the mass% difference does not necessarily have to be within 10% for all of the mainly contained chemical components.

[0074] As shown in Fig. 2, the repair method includes a second step of kneading powder 2 and a sodium silicate aqueous solution 4 in a kneading container 20 to generate a kneaded material 3, which is used as a second repair material 11. The sodium silicate aqueous solution 4 is adjusted in amount to be added depending on the application conditions during repair, and adjusted so that the kneaded material 3 has a viscosity or hardness that makes it easy to apply. Next, as shown in Fig. 1, the repair method includes a third step of applying and / or filling the second repair material 11 to the portion of the sleeve 16 or the crucible to be repaired.

[0075] Repair materials A2 to F2 shown in Fig. 3 are examples of the first repair material 1. Repair materials A2 to F2 are kneaded with a sodium silicate aqueous solution 4 to generate a kneaded material 3, which is used as a second repair material 11. Repair materials A3 to F3 shown in Fig. 4 are examples of the second repair material 11. Since the second repair material 11 is produced by kneading each of the repair materials A2 to F2 with the sodium silicate aqueous solution 4 during the production process, the mass percentages of the chemical components contained in the repair materials A3 to F3 change, but the amount of change is small.

[0076] The mass percentage of aluminum oxide and magnesium oxide contained in repair materials A3 to F3 is slightly lower than that of repair materials A2 to F2. This is because the relative proportion is reduced by the addition of sodium silicate aqueous solution 4. The mass percentage of silicon dioxide is also slightly increased. This is because silicon dioxide derived from sodium silicate is added by the sodium silicate aqueous solution 4. However, the difference in mass percentage of aluminum oxide, magnesium oxide, and silicon dioxide contained in repair materials A3 to F3, which are the second repair material 11, from that contained in sleeves A1 to F1 is within 10%.

[0077] Furthermore, as a result of repair using the repair method, the difference between the linear thermal expansion coefficient at 1500°C of the second repair material 11 applied and / or filled to the area to be repaired and the linear thermal expansion coefficient at 1500°C of the sleeve 16 or crucible to be repaired is within 0.5%.

[0078] <Effects of the repair method according to the third aspect of the present invention> The repair method according to the third aspect of the present invention described above has the following effects. In the first step of the repair method, the difference between the mass % of the specific chemical component contained in the powder 2 and the mass % of the specific chemical component contained in the sleeve 16 or crucible to be repaired is within 10%. Therefore, the repair method can reduce cracks even if the second repair material 11 is exposed to temperature changes after repair.

[0079] Furthermore, when the specific chemical component is aluminum oxide, the difference between the mass % of aluminum oxide contained in the first repair material 1 and the mass % of aluminum oxide contained in the sleeve 16 or crucible to be repaired is within 10%. The second repair material 11 is produced by kneading the first repair material 1 with the sodium silicate aqueous solution 4, so the difference in mass % of aluminum oxide contained in the repair object is small. Therefore, the repair method can reduce cracks even if the second repair material 11 is exposed to temperature changes after repair.

[0080] Furthermore, when the specific chemical component is magnesium oxide, the difference in mass % of magnesium oxide contained in the first repair material 1 and the mass % of magnesium oxide contained in the sleeve 16 or crucible to be repaired is within 10%. The second repair material 11 is produced by kneading the first repair material 1 with the sodium silicate aqueous solution 4, so the difference in mass % of magnesium oxide contained in the repair object is small. Therefore, the repair method can reduce cracks even if the second repair material 11 is exposed to temperature changes after repair.

[0081] Furthermore, when the specific chemical component is silicon dioxide, the difference between the mass % of silicon dioxide contained in the first repair material 1 and the mass % of silicon dioxide contained in the sleeve 16 or crucible to be repaired is within 10%. The second repair material 11 is produced by kneading the first repair material 1 and the sodium silicate aqueous solution 4, so the difference in mass % of silicon dioxide contained in the repair object is small. Therefore, the repair method can reduce cracks even if the second repair material 11 is exposed to temperature changes after repair.

[0082] The above-described effects have been described individually for the chemical components contained in the sleeve 16 or crucible that is the repair target. In contrast, as described in the effects of the first repair material 1 according to the first embodiment and the second repair material 11 according to the second embodiment, when the sleeve 16 or the crucible contains multiple chemical components, the effect is greater if the difference in mass% between each chemical component and the mass% of each chemical component contained in the selected first repair material 1 is within 10%. Similarly, the difference in mass% between the first repair material 1 and all chemical components contained in the repair target does not necessarily have to be within 10%.

[0083] According to the repair method, the difference between the linear thermal expansion coefficient at 1500°C of the kneaded material 3 applied and / or filled in the repair target area and the linear thermal expansion coefficient at 1500°C of the sleeve 16 or the crucible is within 0.5% as shown in Fig. 4. Therefore, since the difference in linear thermal expansion coefficient is small, even if the kneaded material 3 in the repaired area is exposed to a temperature change after repair, cracks caused by the difference in linear thermal expansion coefficient can be reduced, and the repair effect can be improved.

[0084] <Problems to be solved and configuration of the third repair material 21 according to the fourth aspect> Next, the third repair material 21 according to the fourth embodiment of the present invention will be described. The conventional example, which is exemplified by the description in Patent Document 1, had the following problems. According to the description in Patent Document 1, a powdered conventional repair material mainly composed of 5 to 30 mass% metal powder, 10 to 40 mass% of one or more selected from copper oxide, iron oxide, and oxidizer, and the remainder being refractory powder, is sprayed onto a surface to be repaired at high temperature with a non-oxygen gas such as nitrogen gas, carbon dioxide gas, or inert gas as a carrier gas. In this case, since there is no regulation of the particle size of the powdered conventional repair material, for example, even if the target to be repaired has a crack smaller than the particle size, the conventional repair material does not penetrate and cannot be repaired. In addition, if a carrier gas is sprayed onto the powdered conventional repair material at the repair site, the conventional repair material may scatter. This causes a problem that the target area to be repaired cannot be sufficiently repaired.

[0085] On the other hand, the third repair material 21 can repair a sleeve 16 or a crucible formed in an induction furnace 15 for melting metal. As shown in Fig. 3, the third repair material 21 includes a powder 22 having a maximum particle size of 1 mm or less and containing 30% or more particles having a particle size of less than 0.1 mm. The powder 22 can be mixed with the sodium silicate aqueous solution 4 to produce a kneaded material 23. More preferably, the powder 22 contains particles having a particle size of less than 0.1 mm in the range of 40% to 60%.

[0086] The third repair material 21 may be capable of repairing a sleeve 16 containing aluminum oxide or a crucible containing aluminum oxide, and the powder 22 may contain aluminum oxide. It is desirable that the difference between the mass % of aluminum oxide contained in the powder 22 and the mass % of aluminum oxide contained in the sleeve 16 or the crucible to be repaired is within 10%.

[0087] It is also desirable that the difference in mass % between the magnesium oxide contained in the powder 22 and the magnesium oxide contained in the sleeve 16 etc. to be repaired be within 10%. Furthermore, it is also desirable that the difference in mass % between the silicon dioxide contained in the powder 2 and the silicon dioxide contained in the sleeve 16 etc. to be repaired be within 10%.

[0088] <Effects of the third repair material 21 according to the fourth embodiment> The third repair material 21 according to the fourth aspect described above has the following effects. The third repair material 21 can repair the sleeve 16 or the crucible of the induction furnace 15. The powder 22 of the third repair material 21 has a maximum particle size of 1 mm or less, and contains particles with a particle size of less than 0.1 mm at 30 mass % or more, so that it is easy to handle. In addition, the third repair material 21 can be easily mixed with the sodium silicate aqueous solution 4 at the construction site to generate the kneaded material 23. In addition, since the particles are fine, the generated kneaded material 23 can be filled into the fine details of the damaged area, as shown in FIG. 1. This enhances the repair effect.

[0089] In addition, the powder 22 of the third repair material 21 preferably has a maximum particle size of 1 mm or less, and particles with a particle size of less than 0.1 mm are between 40% and 60% by mass, so that it is easy to handle and easier to generate a kneaded material 23 with the sodium silicate aqueous solution 4. The powder 22 contains particles with a particle size of 0.1 mm or more and 1 mm or less at a certain ratio, so that it is easier to knead than when all the particles are less than 0.1 mm. In addition, since the particles are fine, the generated kneaded material 23 can be filled into the details of the damaged area as shown in FIG. 1. Therefore, the repair effect can be improved. The above is an effect due to the fact that the maximum particle size is 1 mm or less and particles with a particle size of less than 0.1 mm are contained at a certain ratio, regardless of the chemical components contained in the third repair material 21.

[0090] The effects when the chemical components contained in the powder 22 are as follows have already been explained for the first repair material 1. That is, the difference between the mass % of aluminum oxide contained in the powder 22 and the mass % of aluminum oxide contained in the sleeve 16 or crucible to be repaired is within 10%. The difference between the mass % of magnesium oxide contained in the powder 22 and the mass % of magnesium oxide contained in the sleeve 16 etc. to be repaired is within 10%. Furthermore, the effects of the difference between the mass % of silicon dioxide contained in the powder 22 and the mass % of silicon dioxide contained in the sleeve 16 etc. to be repaired being within 10% are the same as those of the first repair material 1.

[0091] <Repair method using third repair material 21 according to the fourth embodiment> Next, a repair method using the third repair material 21 according to the fourth embodiment will be described. The repair method using the third repair material 21 may omit the step of selecting the powder 22 for the main chemical components contained in the sleeve 16 or the crucible, as compared to the case using the first repair material 1. In other words, it is not necessary to select the type of powder 22 depending on the chemical components contained in the sleeve 16 or the crucible that is the repair target. The repair method using the third repair material 21 is similar to the step using the first repair material 1 already described, except for the selection of the powder 22. EXAMPLES

[0092] Next, examples of the first repair material 1 and the second repair material 11 of the present invention will be described with reference to Figures 3 and 4. As shown in Figure 3, in the examples, six types of sleeves 16, A1 to F1, were selected as the repair target, and repair materials A2 to F2 were selected as the first repair material 1 having six types of powder 2 suitable for repair.

[0093] As shown in FIG. 4, the repair materials A2 to F2, which are the first repair material 1 containing the powder 2, and the sodium silicate aqueous solution 4 were mixed to produce the second repair material 11 containing the kneading material 3, which are the repair materials A3 to F3. The mass% of the chemical components of the repair materials A3 to F3 is the value measured immediately after the repair materials A2 to F2 and the sodium silicate aqueous solution 4 are mixed to produce the kneading material 3, and the value measured after a certain time has passed since applying or filling the repair object, and there is no change between the two. The mass% of the chemical components of the repair materials A3 to F3 varies depending on the amount of the sodium silicate aqueous solution 4 used when kneading, but the kneading material 3 is kneaded to a viscosity or hardness that makes it easy to repair. The sleeves A1 to F1 are the same as those in FIG. 3.

[0094] In sleeves A1 to C1 shown in Figures 3 and 4, the metal to be treated is, for example, cast steel or special steel. In sleeves D1 and E1, the metal to be treated is, for example, cast steel, special steel, or general steel. In sleeve F1, the metal to be treated is, for example, cast iron. Below, the main chemical components contained therein, aluminum oxide, magnesium oxide, and silicon dioxide, will be described.

[0095] <About aluminum oxide> As shown in FIG. 3, the first repair material 1 including the powder 2 is suitable for the repair materials A2 to F2 with the same alphabetical symbols as the sleeves A1 to F1. All of the sleeves A1 to F1 contain aluminum oxide. In contrast, all of the repair materials A2 to F2 contain aluminum oxide. The differences between the mass% of aluminum oxide of each of the sleeves A1 to F1 and the mass% of aluminum oxide of each of the repair materials A2 to F2 are 5.7% for A1 and A2, 6.3% for B1 and B2, 3.5% for C1 and C2, 2.9 to 8.9% for D1 and D2, 1.2% for E1 and E2, and 5.2% for F1 and F2. That is, all the differences are within 10% as absolute values.

[0096] The first repair material 1, repair materials A2 to F2, were mixed with a sodium silicate aqueous solution 4 to generate a mixed material 3, which was used as the second repair material 11, repair materials A3 to F3. As shown in Figure 4, the differences between the mass% of aluminum oxide contained in the sleeves A1 to F1 and the mass% of aluminum oxide contained in the repair materials A3 to F3 are 1.5% for A1 and A3, 0.3% for B1 and B2, 0.1% for C1 and C2, 0.1% to 0.6% for D1 and D2, 7.8% for E1 and E2, and 3.6% for F1 and F2. In other words, all differences are within 10% as absolute values.

[0097] Therefore, if repair materials A3 to F3 are used to repair sleeves A1 to F1, the linear thermal expansion coefficients of the materials will be close to each other, so that the occurrence of cracks can be reduced even when temperature changes are applied. For sleeves A1 to F1 that contain a large amount of aluminum oxide by mass, the effect after repair is increased by selecting a first repair material 1 that contains a similar amount of aluminum oxide by mass. The effect is particularly great for sleeves A1, B1, D1, and E1.

[0098] <About Magnesium Oxide> Next, as shown in Figure 3, magnesium oxide is contained in sleeves A1, B1, C1, and E1. The difference in mass% of magnesium oxide contained in repair materials A2, B2, C2, and E2 is 2.6% for A1 and A2, 3.3% for B1 and B2, 1.5% for C1 and C2, and 0.8% for E1 and E2, respectively. In other words, all differences are within 10% in absolute value. In particular, for sleeve C1, which has a large mass% of magnesium oxide, the mass% of magnesium oxide contained in repair material C2, which is applied powder 2, is important.

[0099] As shown in Fig. 4, the difference in mass % of magnesium oxide contained in repair material C3 obtained by kneading repair material C2 of powder 2 with sodium silicate aqueous solution 4 is 7.3% compared to the mass % of magnesium oxide contained in sleeve C1 to be repaired. In other words, the difference in mass % of magnesium oxide contained in repair material C3 and sleeve C1 is within 10% in absolute value. Therefore, when repair material C3 is used to repair sleeve C1 to be repaired, the linear thermal expansion coefficients of both materials become close to each other, so that the occurrence of cracks, etc. can be reduced even when temperature changes are applied.

[0100] <About silicon dioxide> Next, as shown in FIG. 3, silicon dioxide is contained in sleeves A1 to F1. The difference in mass% of silicon dioxide contained in each of repair materials A2 to F2 is 1.5% for A1 and A2, 0.7% for B1 and B2, 0.5% for C1 and C2, 2.8% for D1 and D2, 0% for E1 and E2, and 5.1% for F1 and F2. In other words, all differences are within 10% in absolute value. In particular, for sleeve F1, which has a large mass% of silicon dioxide, the mass% of silicon dioxide contained in repair material F2, which is applied powder 2, is important.

[0101] 4, the difference between the mass % of silicon dioxide contained in repair material F3, which is a mixture of repair material F2 of powder 2 and sodium silicate aqueous solution 4, and the mass % of silicon dioxide contained in the sleeve F1 to be repaired is 6.7%, which is within 10%. Therefore, when repair material F2 is used to repair sleeve F1 to be repaired, the linear thermal expansion coefficients of both materials become close to each other, so that the occurrence of cracks, etc. can be reduced even when a temperature change is applied.

[0102] <Test results after repair using the first repair material 1> As described above, suitable repair materials A2 to F2 were selected for the sleeves A1 to F1, and repair materials A3 to F3 were produced as the mixed material 3. As a result, as shown in Fig. 4, the difference range of the linear thermal expansion coefficient at 1500°C between the sleeves A1 to F1 and the repair materials A3 to F3 was all within 0.5% in absolute value.

[0103] The bottom row of Figure 4 is a column showing the presence or absence of cracks after the test. The results show that a thermal shock test was repeated 10 times, with one cycle consisting of exposure to a 1000°C environment for three hours followed by air cooling. The test results after repairs were made to sleeves A1 to F1 were all good, with no problems such as cracks or peeling. In other words, because the linear thermal expansion coefficients of the sleeves A1 to F1 to be repaired and the repair materials A3 to F3 are close, cracks can be reduced even when a temperature change is applied to the repaired area, resulting in a great repair effect. [Explanation of symbols]

[0104] 1, 21, A2, B2, C2, D2, E2, F2 First repair material 2, 22 powder 3, 23 Mixing materials 4. Sodium silicate solution 11, A3, B3, C3, D3, E3, F3 Second Repair Material 15 Induction furnace 16, A1, B1, C1, D1, E1, F1 sleeves

Claims

1. A repair material capable of repairing a sleeve or a crucible containing a specific chemical component among components formed in an induction furnace for melting metal, Equipped with powder, The difference between the mass% of the specific chemical component contained in the powder and the mass% of the specific chemical component contained in the sleeve or the crucible to be repaired is within 10%; The powder is a first repair material capable of forming a kneading material.

2. The first repair material according to claim 1 , wherein the specific chemical component is aluminum oxide.

3. The first repair material according to claim 1 , wherein the specific chemical component is magnesium oxide.

4. The first repair material according to claim 1 , wherein the specific chemical component is silicon dioxide.

5. The first repair material according to any one of claims 1 to 4, wherein the powder has a maximum particle size of 1 mm or less and contains 30% or more particles with a particle size of less than 0.1 mm.

6. The first repair material according to any one of claims 1 to 4, wherein the powder has a maximum particle size of 1 mm or less, and particles with a particle size of less than 0.1 mm are contained in a range of 40% to 60%.

7. A repair material capable of repairing a sleeve or a crucible containing a specific chemical component among components formed in an induction furnace for melting metal, Equipped with mixing material, For the specific chemical components contained in the sleeve or the crucible, A second repair material in which the difference between the mass percentage of the specific chemical component contained in the kneading material and the mass percentage of the specific chemical component contained in the sleeve or crucible to be repaired is within 10%.

8. The second repair material according to claim 7 , wherein the specific chemical component is aluminum oxide.

9. The second repair material according to claim 7 , wherein the specific chemical component is magnesium oxide.

10. The second repair material according to claim 7 , wherein the specific chemical component is silicon dioxide.

11. A second repair material described in any one of claims 7 to 10, wherein the difference between the linear thermal expansion coefficient of the kneaded material at 1500°C and the linear thermal expansion coefficient of the sleeve or crucible to be repaired at 1500°C is within 0.5%.

12. A method for repairing a sleeve or crucible containing a specific chemical component among components formed in an induction furnace for melting metal, comprising the steps of: A first step of selecting a first repair material comprising a powder; A second step of kneading the first repair material with a sodium silicate aqueous solution to produce a second repair material; A third step of applying and / or filling the second repair material to the sleeve or the crucible to be repaired, A repair method in which the first repair material selected in the first step has a difference between the mass percentage of the specific chemical component contained in the powder and the mass percentage of the specific chemical component contained in the sleeve or crucible to be repaired of within 10%.

13. The repair method according to claim 12 , wherein the specific chemical component is aluminum oxide.

14. The repair method according to claim 12, wherein the specific chemical component is magnesium oxide.

15. The repair method according to claim 12, wherein the specific chemical component is silicon dioxide.

16. A repair method described in any one of claims 12 to 15, wherein the difference between the linear thermal expansion coefficient at 1500°C of the second repair material applied and / or filled to the sleeve or crucible to be repaired and the linear thermal expansion coefficient at 1500°C of the sleeve or crucible to be repaired is 0.5% or less.

Citation Information

Patent Citations

  • Hot repairing method of lining castable refractory of refining vessel such as electric furnace

    JP2006220376A

  • Non-aqueous press-fitting material for repair

    JP2015160754A

  • Spraying material for repair of joint of coke oven

    JP2016003313A

  • Hot repairing method for industrial furnace

    JP2004028504A